Young Muslim 2 (Singapore : Afia Interactive Media, 1999)
Young Muslim 2 is a sequel to the popular Young Muslim that has been used by madrasahs as part of their curriculum. In this multimedia cd-rom, you will find 38 more doas, 44 hadis and juz Ammas. Plus, there are quizzes that test your memory, usage of the doa, understanding of the hadis and many more.
Windows 95, CD-ROM drive
Keywords: Islam -- Customs and practices; Prayer -- Islam; Youth, Muslim -- Religious life